LAYANAN BIMBINGAN KELOMPOK SECARA DARING MELALUI TEKNIK PROBLEM SOLVING UNTUK MOTIVASI BELAJAR SISWA SMP KELAS VIII - Dewi, Panny Fitria; Rohaeti, Euis Eti; Alawiyah, Tuti (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
Learning motivation is something that must be owned by every individual, especially for students, with the motivation to learn students can be encouraged to develop more advanced and can achieve their learning goals. Students' learning motivation during this pandemic has decreased due to several factors and obstacles felt by students. These factors come from external factors and internal factors. The purpose of this study was to find out that group guidance services boldly through problem solving techniques can be used for student motivation. This study uses a qualitative research method with a descriptive approach. The subjects of this study were students of class VIII A at SMP Negeri 1 Cipatat which consisted of 9 students, 7 female students and 2 male students. Data collection techniques using observation and interviews. Group guidance services are provided in 2 meetings. The results of the research obtained after being given the service that students experienced changes that were seen based on aspects of their learning motivation, namely students became more enthusiastic in daring learning, had curiosity, and students wanted to know the wider world so as to increase student learning motivation.